The relationship between the habit of brushing teeth before sleeping at night and the caries status of children aged 9-12 years: relationship between the habit of brushing teeth before sleeping at night and the caries status of children aged 9-12 years - Sitti Fadhilla Oemar M; Sari Aldilawati; Azzahra Anindya (Makassar Dental Journal PDGI Makassar, 2024)
The habit of brushing teeth is very helpful in cleaning food residue on the teeth. Primary school age is the right time to provide a solid foundation for quality human beings, because health is the main factor to determine their quality. This study aimed to deter-mine the relationship between the habit of brushing teeth before going to bed at night on the caries status of children aged 9-12 years. Analytical observational study using cross sectional design. Spearman statistical test was used in this study involving 60 samples. Based on the Spearman Rho correlation test, the p-value was 0.01 or p<0.05. The correlation coefficient shows a value of 0.722 which means the correlation is strong. This means that there is a significant relationship between the habit of brushing teeth at night and the caries status of children aged 9-12 years at SDN 57 Pare-Pare. It is concluded that the habit of brushing teeth before going to bed at night affects the caries status of children aged 9-12 years.